CALCULATION OF ELECTRONIC PAGING FUNCTION Al2SiO4 TOPAZ (F, OH) 2 - Flores, Luis (2006)
By TB-LMTO-ASA method, calculation of the density of states is performed. charge density and electronic localization function topaz and its elements, with the aim of studying the links of its crystalline structure, that when subsequently irradiated with neutrons in the nucleus epiiérmicos reactor RP-1 O, defects will occur in the crystal lattice, changing its optical response. The results show that the aluminum atoms have higher mobilization probabilicfad, this is due to the weak link of the electron delocalization product